Preparation method of 7075 aluminum alloy micro-arc oxidation ceramic film layer

By solid solution and aging treatment of 7075 aluminum alloy, and using specific electrolyte components during the microarc oxidation process, a dense ceramic film layer is solved, and the corrosion resistance of aluminum alloy is significantly improved.

CN119615328APending Publication Date: 2025-03-14CHANGZHOU INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411903737.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Due to its active chemical properties and poor corrosion resistance, 7075 aluminum alloy is prone to pitting, intergranular corrosion, stress corrosion and peeling corrosion in applications, limiting its further application.

Method used

By solid solution treatment and non-isothermal aging treatment on the 7075 aluminum alloy, a fine diffuse secondary precipitation phase is formed, and a constant current mode, optimized arc conditions and specific electrolyte components, including ytterbium oxide and zinc oxide, are used during the microarc oxidation process to form a dense ceramic film layer.

Benefits of technology

It improves the density and corrosion resistance of the ceramic film layer, and enhances the wear and corrosion resistance of the 7075 aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of corrosion-resistant coatings, and discloses a preparation method of a 7075 aluminum alloy micro-arc oxidation ceramic film layer. Comprising the following operation steps that 1, the 7075 aluminum alloy is sequentially subjected to solution treatment and non-isothermal aging treatment, and the prefabricated 7075 aluminum alloy is obtained; and 2, the prefabricated 7075 alloy is immersed into the electrolyte, the prefabricated 7075 alloy serves as an anode, a stainless steel container with a cold system serves as a cathode, micro-arc oxidation is conducted in a constant-current mode, and a finished product containing the micro-arc oxidation ceramic film layer is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of corrosion-resistant coatings, and in particular to a method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer. Background Art

[0002] 7075 high-strength aluminum alloy has the characteristics of low density, high strength, good processing performance and good welding performance. It is an important lightweight and high-strength structural material and is widely used in the fields of aviation industry and civil industry. However, due to the active chemical properties of 7xxx series aluminum alloys, pitting corrosion, intergranular corrosion, stress corrosion and exfoliation corrosion will occur, and its poor corrosion resistance greatly limits its further application.

[0003] In recent years, people have conducted a lot of research on improving the wear resistance and corrosion resistance of aluminum and its aluminum alloys. It was found that by in-situ generating a dense ceramic oxide film on the alloy surface, it can effectively prevent it from contacting the external environment, thereby increasing the corrosion resistance of the alloy; the micro-arc oxidation process can generate a dense oxide film on the surface of aluminum alloy, but there will be many micropores and microcracks on its surface. These micropores and microcracks will be preferentially corroded by corrosive media, thus limiting its application in the field of corrosion-resistant coating technology.

[0004] In summary, it is of great significance to solve the above problems and provide a method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer comprises the following steps: Step 1: subjecting the 7075 aluminum alloy to solution treatment and non-isothermal aging treatment in sequence to obtain a prefabricated 7075 aluminum alloy; Step 2: Immerse the prefabricated 7075 alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode, and perform micro-arc oxidation in a constant current mode to obtain a finished product containing a micro-arc oxidation ceramic film layer.

[0007] The optimal conditions for micro-arc oxidation are: the current is 3-7A / dm 2 , frequency is 300~600Hz, duty cycle is 20%; time is 15~25 minutes.

[0008] The non-isothermal aging treatment process is more optimized as follows: the prefabricated 7075 aluminum alloy is heated to 120-210°C at a heating rate of 20-30°C / h, then cooled to 100-160°C at a cooling rate of 20-30°C / h, and then cooled to room temperature.

[0009] The process of the solution treatment is more optimized: keeping the 7075 alloy at 470-500°C for 30-40 minutes, heating to 480-550°C for 30-35 minutes, cooling to 400-420°C at a rate of 25-30°C / h for 30-40 minutes for high temperature pre-precipitation, and quenching in cold water at 20-25°C.

[0010] More optimally, the raw materials of the electrolyte include the following components: 5~15g / L Na2SiO3, 1~4g / L KOH, 1~3g / L NaF, 4~8g / L ZnO, and 2~5g / L Yb2O3.

[0011] Further optimized, the raw materials of the electrolyte include the following components: 8~10g / L Na2SiO3, 2~3g / L KOH, 1.5~2.5g / L NaF, 5~6g / L ZnO, and 3~4g / L Yb2O3.

[0012] In the scheme, before micro-arc oxidation, the Yb2O3 powder was placed in an ethanol solution and ultrasonically dispersed for half an hour, and then mixed with the electrolyte and mechanically stirred for 2 hours.

[0013] More optimally, the electrolyte further comprises 0.7-1.5 g / L of sulfonated branched polyetheretherketone and 2-3 g / L of solid lubricant; the solid lubricant is boron nitride and polytetrafluoroethylene in a mass ratio of (2-3):1.

[0014] The more optimized preparation method of the sulfonated branched polyetheretherketone is as follows: (1) uniformly mixing 1,4-di(bromomethyl)benzene, hexafluoropropylene dimer, anhydrous potassium chloride and N,N-dimethylacetamide, heating to 75-80°C, reacting for 20-24 hours, washing and drying to obtain an intermediate product; (2) dissolving the intermediate product, 4-hydroxy-1-butanesulfonic acid, potassium carbonate and sodium carbonate in cyclobutane sulfone, adding toluene, reacting at 130-140°C for 2-3 hours under a nitrogen atmosphere, heating to 170-180°C and reacting for 4-5 hours to obtain a sulfonated branched polyetheretherketone.

[0015] More optimally, the raw materials of the intermediate product include the following components: 2 to 3 parts of 1,4-di(bromomethyl)benzene, 4 to 6 parts of hexafluoropropylene dimer, 2 to 3 parts of anhydrous potassium chloride, and 40 to 50 parts of N,N-dimethylacetamide in parts by mass; the raw materials of the sulfonated branched polyetheretherketone include the following components: 2 to 3 parts of the intermediate product, 5 to 7 parts of 4-hydroxy-1-butanesulfonic acid, 0.4 to 0.5 parts of potassium carbonate, 0.6 to 1 parts of sodium carbonate, 22 to 25 parts of cyclopentane sulfone, and 15 to 20 parts of toluene in parts by mass.

[0016] More optimally, during the micro-arc oxidation process, an external electric field is set; the external electric field is a DC electric field, and the direction of the external electric field is consistent with the direction of the electric field of micro-arc oxidation; the voltage is 10~30kV; and the electric field frequency is 100~270Hz.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention first performs a solid solution treatment and a non-isothermal aging treatment on the 7075 aluminum alloy in sequence, so that a fine dispersed secondary precipitate phase can be obtained; then, in the micro-arc oxidation constant current mode, the secondary precipitate phase can hinder the movement of electrons, thereby increasing the voltage of the micro-arc oxidation, thereby increasing the thickness of the ceramic film layer; and the fine phase helps to form a smaller discharge channel, which is beneficial to reducing the micropore diameter of the ceramic film layer, thereby enhancing the density of the ceramic film layer, and thus improving the corrosion resistance of the 7075 aluminum alloy.

[0018] During the micro-arc oxidation process, the formation of pores and cracks often leads to a decrease in the density of the film layer, affecting the performance of the ceramic film layer. In order to improve the density, the scheme adds ytterbium oxide (Yb2O3) and zinc oxide (ZnO) to the electrolyte of micro-arc oxidation. The addition of ytterbium oxide can optimize the micro-arc oxidation process and reduce the formation of pores, thereby enhancing the density and overall integrity of the ceramic film layer. Zinc oxide forms a cluster structure on the surface of the ceramic film layer, which will fill the micropores to a certain extent, reduce the cracks and porosity of the ceramic film layer, and thus improve the corrosion resistance and overall density of the ceramic film layer.

[0019] In order to further reduce cracks and porosity, boron nitride and polytetrafluoroethylene are added to the electrolyte as solid lubricants. Both polytetrafluoroethylene (PTFE) and boron nitride have good self-lubricity and low friction coefficient. The synergistic effect of the two can effectively enable aluminum alloy to still exhibit good lubrication effect under high friction and high load conditions. Adding the two as solid lubricants to the electrolyte can effectively reduce the direct friction between the contact surfaces, thereby reducing wear.

[0020] However, boron nitride is not conductive, so a surfactant is added to the electrolyte to make its surface have a negative charge, which is enriched at the anode during the micro-arc oxidation process, thereby improving the efficiency of boron nitride addition; however, micro-arc oxidation is a high-energy, high-temperature surface treatment technology; in this process, arc discharge occurs on the surface of the metal substrate, and the local temperature can reach several thousand degrees, forming a high-temperature plasma zone, which will cause ablation of polytetrafluoroethylene.

[0021] In the scheme, a precursor is obtained by reacting 1,4-di(bromomethyl)benzene with a hexafluoropropylene dimer; the fluorine group on the precursor is then reacted with the hydroxyl group on 4-hydroxy-1-butane sulfonic acid to obtain a sulfonated branched polyetheretherketone; using it as a surfactant, the fluorine element in the hexafluoropropylene dimer has strong chemical stability and can enhance the corrosion resistance of the oxide film; the sulfonic acid group therein is hydrophilic, which can help improve the interaction between polyetheretherketone and polytetrafluoroethylene, thereby enhancing the mechanical strength and thermal stability of polytetrafluoroethylene and reducing ablation; and by means of an external electric field, the uniformity of the ceramic film layer during the oxidation process is improved, the formation of local hot spots is further reduced, and the performance of the ceramic film layer is optimized; it can also promote the grain growth of some metal oxides in the ceramic film layer, and the structure of these crystalline oxides is usually more stable, which can provide better thermal stability and mechanical strength. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] In the following specific implementation methods, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: the CAS number of Na2SiO3 is 6834-92-0; the CAS number of KOH is 1310-58-3; the CAS number of NaF is 7681-49-4; the item number of ZnO is S24314, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the item number of Yb2O3 is S41975, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; the CAS number of 1,4-di(bromomethyl)benzene is 623-24-5; the CAS number of hexafluoropropylene dimer is The CAS number of 4-hydroxy-1-butanesulfonic acid is 26978-64-3; the CAS number of potassium carbonate is 584-08-7; the CAS number of sodium carbonate is 497-19-8; the CAS number of cyclopentane sulfone is 126-33-0; the CAS number of toluene is 108-88-3; the model of boron nitride is HBN-0100, purchased from Zhejiang Yamei Nano Technology Co., Ltd.; the product number of polytetrafluoroethylene is S24392, purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0024] Embodiment 1: A method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer, comprising the following steps: Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and heat it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 120°C at a rate of 20°C / h, then immediately cool it to 100°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 5 g / L Na2SiO3, 2 g / L KOH, 1 g / L NaF, 6 g / L ZnO, and 2 g / L Yb2O3.

[0025] Embodiment 2: A method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer, comprising the following steps: Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 160°C at a rate of 20°C / h, then immediately cool it to 120°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, and 3 g / L Yb2O3.

[0026] Embodiment 3: A method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film layer, comprising the following steps: Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 160°C at a rate of 20°C / h, then immediately cool it to 120°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 15 g / L Na2SiO3, 5 g / L KOH, 2 g / L NaF, 8 g / L ZnO, and 4 g / L Yb2O3.

[0027] Example 4 Based on Example 2, 0.8 g / L of sulfonated branched polyetheretherketone and 2 g / L of solid lubricant were added to the electrolyte; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 160°C at a rate of 20°C / h, then immediately cool it to 120°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, 3 g / L Yb2O3, 0.8 g / L sulfonated branched polyetheretherketone, and 2 g / L solid lubricant; wherein the solid lubricant is boron nitride and polytetrafluoroethylene in a mass ratio of 2.5:1; The preparation method of the sulfonated branched polyetheretherketone is as follows: (1) uniformly mixing 2.2 parts of 1,4-di(bromomethyl)benzene, 5 parts of hexafluoropropylene dimer, 2.5 parts of anhydrous potassium chloride, and 45 parts of N,N-dimethylacetamide, heating to 75°C, reacting for 20 hours, washing, and drying to obtain an intermediate product; (2) dissolving 2 parts of the intermediate product, 5.5 parts of 4-hydroxy-1-butanesulfonic acid, 0.4 parts of potassium carbonate, and 0.6 parts of sodium carbonate in 22 parts of cyclopentane sulfone, adding 17 parts of toluene, reacting at 135°C for 2 hours under a nitrogen atmosphere, and heating to 175°C for 4 hours to obtain a sulfonated branched polyetheretherketone.

[0028] Example 5 is based on Example 4, and an external electric field is introduced during micro-arc oxidation; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and heat it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 120°C at a rate of 20°C / h, then immediately cool it to 100°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, 3 g / L Yb2O3, 0.8 g / L sulfonated branched polyetheretherketone, and 2 g / L solid lubricant; wherein the solid lubricant is boron nitride and polytetrafluoroethylene in a mass ratio of 2.5:1; The preparation method of the sulfonated branched polyetheretherketone is as follows: (1) uniformly mixing 2.2 parts of 1,4-di(bromomethyl)benzene, 5 parts of hexafluoropropylene dimer, 2.5 parts of anhydrous potassium chloride, and 45 parts of N,N-dimethylacetamide, heating to 75°C, reacting for 20 hours, washing, and drying to obtain an intermediate product; (2) dissolving 2 parts of the intermediate product, 5.5 parts of 4-hydroxy-1-butanesulfonic acid, 0.4 parts of potassium carbonate, and 0.6 parts of sodium carbonate in 22 parts of cyclopentane sulfone, adding 17 parts of toluene, reacting at 135°C for 2 hours under a nitrogen atmosphere, and heating to 175°C for 4 hours to obtain a sulfonated branched polyetheretherketone.

[0029] Comparative Example 1 Based on Example 2, the raw materials of the electrolyte were replaced with 10 g / L Na2SiO3, 1 g / L KOH, and 3 g / L (NaPO3)6; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and heat it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 120°C at a rate of 20°C / h, then immediately cool it to 100°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 1 g / L KOH, and 3 g / L (NaPO3)6.

[0030] Comparative Example 2 is based on Example 2, but the 7075 aluminum alloy is not subjected to non-isothermal aging treatment; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and keep it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C to obtain prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, and 3 g / L Yb2O3.

[0031] Comparative Example 3 is based on Example 5, and only boron nitride is introduced into the solid lubricant; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and heat it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 120°C at a rate of 20°C / h, then immediately cool it to 100°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, 3 g / L Yb2O3, 0.8 g / L sulfonated branched polyetheretherketone, and 2 g / L boron nitride; The preparation method of sulfonated branched polyetheretherketone is as follows: (1) uniformly mixing 2.2 parts of 1,4-di(bromomethyl)benzene, 5 parts of hexafluoropropylene dimer, 2.5 parts of anhydrous potassium chloride and 45 parts of N,N-dimethylacetamide, heating to 75°C, reacting for 20 hours, washing and drying to obtain an intermediate product; (2) dissolving 2 parts of the intermediate product, 5.5 parts of 4-hydroxy-1-butanesulfonic acid, 0.4 parts of potassium carbonate and 0.6 parts of sodium carbonate in 22 parts of cyclopentane sulfone, adding 17 parts of toluene, reacting at 135°C for 2 hours under a nitrogen atmosphere, heating to 175°C and reacting for 4 hours to obtain a sulfonated branched polyetheretherketone.

[0032] Comparative Example 4 is based on Example 5, and a conventional anionic surfactant is added to the electrolyte; Step 1: Place the 7075 aluminum alloy in a box-type resistance furnace at 470°C for 30 minutes, heat it to 480°C for 30 minutes, cool it to 400°C at a rate of 30°C / h and heat it for 30 minutes for high-temperature pre-precipitation, and quench it in cold water at 20°C; then place it in a box-type resistance furnace and heat it to 120°C at a rate of 20°C / h, then immediately cool it to 100°C at a rate of 20°C / h, and then cool it to room temperature with the furnace to obtain a prefabricated 7075 aluminum alloy; Step 2: Place the prefabricated 7075 aluminum alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode. Use the constant current mode at a current of 6A / dm 2 Under the conditions of a frequency of 500 Hz and a duty cycle of 20%, micro-arc oxidation was performed for 20 minutes to obtain a finished product containing a micro-arc oxidation ceramic film layer; The raw materials of the electrolyte include the following components: 10 g / L Na2SiO3, 2 g / L KOH, 2 g / L NaF, 8 g / L ZnO, 3 g / L Yb2O3, 0.8 g / L sodium dodecylbenzene sulfonate, and 2 g / L solid lubricant; the solid lubricant is boron nitride and polytetrafluoroethylene in a mass ratio of 2.5:1.

[0033] Detection test: The samples prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to friction and wear tests using a HT-600 high temperature friction and wear testing machine, and the masses before and after wear were recorded, with the difference between the masses before and after wear being the mass loss. The porosity of the ceramic film surfaces of Examples 1 to 5 and Comparative Examples 1 to 4 was analyzed using imageJ software. The self-corrosion potential of Examples 1 to 5 and Comparative Examples 1 to 4 was tested using a potentiodynamic polarization curve.

[0034]

[0035] Table 1 Conclusion: By comparing Examples 1 to 3, it is found that Example 2 is the optimal solution; Example 4 is based on Example 2, and 0.8 g / L of sulfonated branched polyetheretherketone and 2 g / L of solid lubricant are added to the electrolyte, and it is found that the mass loss and porosity are reduced, and the self-corrosion potential is increased, indicating that the ceramic film layer on the 7075 aluminum alloy is more stable and has better corrosion resistance; Example 5 is based on Example 4, and an external electric field is introduced during micro-arc oxidation; the migration speed of ions in the electrolyte is enhanced, the uniformity of the oxidation process is improved, and the generation of local hot spots is further reduced, thereby optimizing the performance of the ceramic film layer.

[0036] Comparative Example 1 is based on Example 2, except that the raw materials of the electrolyte are replaced with 10 g / L Na2SiO3, 1 g / L KOH, and 3 g / L (NaPO3)6; this results in a decrease in its performance, because ytterbium oxide (Yb2O3) and zinc oxide in the electrolyte can optimize the micro-arc oxidation process, reduce the formation of pores and cracks, and thus improve the corrosion resistance and overall density of the ceramic film layer; Comparative Example 2 is based on Example 2, except that the 7075 aluminum alloy is not subjected to non-isothermal aging treatment; this results in a decrease in its performance, because non-isothermal aging treatment can obtain fine and dispersed secondary precipitates; and under micro-arc oxidation conditions, these secondary precipitates can hinder the free movement of electrons, increase the voltage of micro-arc oxidation, and thus increase the thickness of the micro-arc oxidation film; and the fine phases help to form smaller discharge channels, thereby reducing the diameter of the micropores of the micro-arc oxidation film and increasing the density and corrosion resistance of the film layer.

[0037] Comparative Example 3 is based on Example 5, and only boron nitride is introduced into the solid lubricant; therefore, its performance is reduced, because boron nitride has self-lubricity and corrosion resistance, and can synergize with polytetrafluoroethylene to improve the performance of 7075 aluminum alloy; Comparative Example 4 is based on Example 5, and a conventional anionic surfactant is added to the electrolyte; resulting in a reduction in the performance of 7075 aluminum alloy; because during the micro-arc oxidation process, arc discharge occurs on the surface of the metal matrix, and the local temperature can be as high as several thousand degrees, forming a high-temperature plasma zone, which will cause ablation of polytetrafluoroethylene; and sulfonated branched polyetheretherketone is used as a surfactant, and the sulfonic acid group is hydrophilic, which helps to improve the interaction between polyetheretherketone and polytetrafluoroethylene, thereby enhancing the mechanical strength and thermal stability of polytetrafluoroethylene and reducing ablation, so the performance of 7075 aluminum alloy can be improved.

[0038] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film, characterized in that: The steps include: Step 1: subjecting the 7075 aluminum alloy to solution treatment and non-isothermal aging treatment in sequence to obtain a prefabricated 7075 aluminum alloy; Step 2: Immerse the prefabricated 7075 alloy in the electrolyte, use the prefabricated 7075 aluminum alloy as the anode, and the stainless steel container with a cooling system as the cathode, and perform micro-arc oxidation in a constant current mode to obtain a finished product containing a micro-arc oxidation ceramic film layer.

2. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: The conditions of the micro-arc oxidation are: the current is 3~7A / dm 2 , frequency is 300~600Hz, duty cycle is 20%; time is 15~25 minutes.

3. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: The process of the non-isothermal aging treatment is: heating the prefabricated 7075 aluminum alloy to 120-210°C at a heating rate of 20-30°C / h, cooling it to 100-160°C at a cooling rate of 20-30°C / h, and then cooling it to room temperature.

4. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: The process of the solution treatment is as follows: keeping the 7075 alloy at 470-500° C. for 30-40 minutes, heating it to 480-550° C. for 30-35 minutes, cooling it to 400-420° C. at a rate of 25-30° C. / h and keeping it for 30-40 minutes for high-temperature pre-precipitation, and quenching it in cold water at 20-25° C.

5. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: The raw materials of the electrolyte include the following components: 5-15 g / L Na2SiO3, 1-4 g / L KOH, 1-3 g / L NaF, 4-8 g / L ZnO, and 2-5 g / L Yb2O3.

6. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: The electrolyte also includes 0.7-1.5 g / L of sulfonated branched polyetheretherketone and 2-3 g / L of solid lubricant; the solid lubricant is boron nitride and polytetrafluoroethylene in a mass ratio of (2-3):

1.

7. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 6, characterized in that: The preparation method of the sulfonated branched polyether ether ketone is as follows: (1) uniformly mixing 1,4-di(bromomethyl)benzene, a hexafluoropropylene dimer, anhydrous potassium chloride and N,N-dimethylacetamide, heating to 75-80° C., reacting for 20-24 hours, washing and drying to obtain an intermediate product; (2) dissolving the intermediate product, 4-hydroxy-1-butane sulfonic acid, potassium carbonate and sodium carbonate in cyclobutane sulfone, adding toluene, reacting at 130-140° C. for 2-3 hours under a nitrogen atmosphere, heating to 170-180° C. for reaction for 4-5 hours to obtain a sulfonated branched polyether ether ketone.

8. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 7, characterized in that: The raw materials of the intermediate product include the following components: 2 to 3 parts of 1,4-di(bromomethyl)benzene, 4 to 6 parts of hexafluoropropylene dimer, 2 to 3 parts of anhydrous potassium chloride, and 40 to 50 parts of N,N-dimethylacetamide, by mass; the raw materials of the sulfonated branched polyetheretherketone include the following components: 2 to 3 parts of the intermediate product, 5 to 7 parts of 4-hydroxy-1-butanesulfonic acid, 0.4 to 0.5 parts of potassium carbonate, 0.6 to 1 parts of sodium carbonate, 22 to 25 parts of cyclopentane sulfone, and 15 to 20 parts of toluene, by mass.

9. The method for preparing a 7075 aluminum alloy micro-arc oxidation ceramic film according to claim 1, characterized in that: During the micro-arc oxidation treatment, an external electric field is set; the external electric field is a DC electric field, and the direction of the external electric field is consistent with the direction of the electric field of micro-arc oxidation; the voltage is 10-30 kV; and the electric field frequency is 100-270 Hz.